Correlation the <112>111 slip with high-temperature tension/compression asymmetry in the single-crystal nickel-based superalloy PWA1483. Issue 6 (3rd June 2023) - Zhang, P.; Li, J.; Yuan, Y.; Gu, Y.F.; Gao, Z.H.; Gong, X.F.; Song, X. L.
Abstract : The yield strength of the [001]-orientated single-crystal nickel-based superalloy PWA1483 is investigated under tension/compression at 1000 and 1100 °C. We found that the compressive yield strength is larger than the tensile strength. Microstructural observations disclose that the dominant deformation modes are stacking fault shearing and microtwinning in compression at 1000 °C, whereas dislocation climb controls the plastic deformation under the other three deformation conditions, although the above two processes also occur. Based on these results, it is deemed that the frequent occurrence of <112>111 slip accounts for the tension/compression asymmetry in the yield strength of PWA1483 at high temperatures. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: The tension/compression asymmetry concerning the yield strength, stacking fault shearing and mcirotwinning at 1000 and 1100 °C in the [001]-oriented single-crystal nickel-based superalloy is uncovered for the first time.